Closed adjective classes and primary adjectives in African Languages - (:unkn) unknown (My University, 2008)
The existence of closed adjective classes (henceforth CAC) has long been recognized for African languages. Although I probably haven't found the earliest mention of this property , Welmers' 1973 statement in 'African Language Structures' is often quoted. Subsequent mentions of CAC are found in Dixon (1977 revised 1982, 1999, 2004), and although he seldom refers to African languages, he has been repeatedly cited since. Yet there has been no attempt to provide a general overview of the phenomenon, and the present paper aims at filling this gap.
Keywords: African Research